The Role of Tourism Village to Increase Local Community Income - Dino Leonandri; Maskarto Lucky Nara Rosmadi (Budapest International Research and Critics University, 2018)
This study aimed at finding and analyzing the role of tourism villages in increasing local people's income. The problem faced is lack of synergy between the local community, local government, and other stakeholders. The method used is a qualitative method with a descriptive explorative approach. From the results of the study, it was found that tourism villages could open employment opportunities, elevate regional culture, and develop economic potential and welfare of the local community who prioritized populist economy based on local wisdom. From this study it can be concluded that the role of village tourism has a significant impact on local communities, especially can increase family income.